Effect of remifentanil hydrochloride administered via constant rate infusion on the minimum alveolar concentration of isoflurane in cats - Ferreira, Tatiana H.; Aguiar, Antonio J. A.; Valverde, Alexander; Teixeira Neto, Francisco José [UNESP]; Steagall, Paulo V. M.; Soares, João H. N. (American Veterinary Medical Association (AVMA), 2009)
Objective - To evaluate the effects of increasing doses of remifentanil hydrochloride administered via constant rate infusion (CRI) on the minimum alveolar concentration (MAC) of isoflurane in cats. Animals - 6 healthy adult cats. Procedures - For each cat, 2 experiments were performed (2-week interval). On each study day, anesthesia was induced and maintained with isoflurane; a catheter was placed in a cephalic vein for the administration of lactated Ringer's solution or remifentanil CRIs, and a catheter was placed in the jugular vein for collection of blood samples for blood gas analyses. On the first study day, individual basal MAC (MAC Basal) was determined for each cat. On the second study day, 3 remifentanil CRIs (0.25, 0.5, and 1.0 μg/kg/min) were administered (in ascending order); for each infusion, at least 30 minutes elapsed before determination of MAC (designated as MAC R0.25, MAC R0.5, and MAC R1.0, respectively). A 15-minute washout period was allowed between CRIs. A control MAC (MAC Control) was determined after the last remifentanil infusion. Results - Mean ± SD MAC Basal and MAC Control values at sea level did not differ significantly (1.66 ± 0.08% and 1.52 ± 0.21%, respectively). The MAC values determined for each remifentanil CRI did not differ significantly. However, MAC R0.25, MAC R0.5, and MAC R1.0, were significantly decreased, compared with MAC Basal, by 23.4 ± 79%, 29.8 ± 8.3%, and 26.0 ± 9.4%, respectively. Conclusions and Clinical Relevance - The 3 doses of remifentanil administered via CRI resulted in a similar degree of isoflurane MAC reduction in adult cats, indicating that a ceiling effect was achieved following administration of the lowest dose.
Keywords: isoflurane; remifentanil; Ringer lactate solution; anesthesia induction; anesthesiological techniques; animal experiment; blood gas analysis; blood sampling; breathing rate; cat; cephalic vein; controlled study; dose response; drug dose increase; female; heart rate; jugular vein; male; minimum lung alveolus concentration; nonhuman; systolic blood pressure; vein catheterization; Anesthetics, Intravenous; Animals; Blood Gas Analysis; Cats; Female; Infusions, Intravenous; Isoflurane; Male; Piperidines; Pulmonary Alveoli; Animalia